Berlin Coquette : Prostitution and the New German Woman, 1890–1933 - Smith, Jill Suzanne, 1972- (Book collections on Project MUSE., 2013)
During the late nineteenth century the city of Berlin developed such a reputation for lawlessness and sexual licentiousness that it came to be known as the "Whore of Babylon." Out of this reputation for debauchery grew an unusually rich discourse around prostitution. This book shows how this discourse transcended the usual cliches about prostitutes and actually explored complex visions of alternative moralities or sexual countercultures including the new morality articulated by feminist radicals, lesbian love, and the new woman.